Comparison of OBGYN postgraduate curricula and assessment methods between Canada and the Netherlands: an auto-ethnographic study - Paternotte, Emma; Dijksterhuis, Marja; Goverde, Angelique; Ezzat, Hanna; Scheele, Fedde (Frontiers in Medicine, 2024)
Introduction Although the Dutch and the Canadian postgraduate Obstetrics and Gynecology (OBGYN) medical education systems are similar in their foundations [programmatic assessment, competency based, involving CanMED roles and EPAs (entrustable professional activities)] and comparable in healthcare outcome, their program structures and assessment methods considerably differ. Materials and methods We compared both countries' postgraduate educational blueprints and used an auto-ethnographic method to gain insight in the effects of training program structure and assessment methods on how trainees work. The research questions for this study are as follows: what are the differences in program structure and assessment program in Obstetrics and Gynecology postgraduate medical education in the Netherlands and Canada? And how does this impact the advancement to higher competency for the postgraduate trainee? Results We found four main differences. The first two differences are the duration of training and the number of EPAs defined in the curricula. However, the most significant difference is the way EPAs are entrusted. In Canada, supervision is given regardless of EPA competence, whereas in the Netherlands, being competent means being entrusted, resulting in meaningful and practical independence in the workplace. Another difference is that Canadian OBGYN trainees have to pass a summative written and oral exit examination. This difference in the assessment program is largely explained by cultural and legal aspects of postgraduate training, leading to differences in licensing practice. Discussion Despite the fact that programmatic assessment is the foundation for assessment in medical education in both Canada and the Netherlands, the significance of entrustment differs. Trainees struggle to differentiate between formative and summative assessments. The trainees experience both formative and summative forms of assessment as a judgement of their competence and progress. Based on this auto-ethnographic study, the potential for further harmonization of the OBGYN PGME in Canada and the Netherlands remains limited.